Reformulasi Hak Kompensasi Pelaku Tindak Pidana Lingkungan Hidup dalam Ruang Lingkup Korporasi Pasca Putusan Bebas (Vrijspraak) - Muhammad Naufal Yasykur; Murshal Senjaya (Jurnal Hukum Lex Generalis, 2025)
This study examines the urgent need to reformulate compensation rights for corporations acquitted (vrijspraak) in environmental criminal cases in Indonesia. Despite being proven not guilty under Law No. 32/2009, corporations still suffer massive and long-term reputational, financial, and operational losses due to protracted proceedings, public stigmatization, and irreversible damage to business opportunities—violating the presumption of innocence and legal certainty. Existing compensation mechanisms remain individual-centric and fail to address systemic corporate harm. The research proposes specific amendments to the Criminal Procedure Code (KUHAP) and related Government Regulations to provide material compensation (lost profits, stock depreciation, business opportunities) and immaterial compensation (official rehabilitation of good name through court announcements and national media), plus state liability for misuse of process, thereby achieving balanced, civilized, and constitutionally mandated justice.